Recovery of Bone Mineral Mass After Upper Limb Fractures in Children and Teenagers. Issue 4 (April 2019) - Maggio, Albane B.R.; Martin, Xavier; Tabard-Fougère, Anne; Steiger, Christina; Dayer, Romain; Delhumeau, Cécile; Ceroni, Dimitri
Abstract : Background: Loss of bone mineral mass and muscle atrophy are predictable consequences of cast-mediated immobilization following wrist and forearm fractures. This study aimed to prospectively determine whether previously reported lower bone mineral mass following immobilization for wrist and forearm fractures in children and teenagers had recovered at 6- and 18-month follow-up. Methods: We recruited 50 children and teenagers who underwent a cast-mediated immobilization for a forearm or wrist fracture. Dual-energy x-ray absorptiometry scans of different skeletal sites were performed at the time of fracture, at cast removal, at 6 and at 18-month follow-up. Injured patients were paired with healthy controls according to sex and age. Dual-energy x-ray absorptiometry values were compared between groups and the injured and uninjured forearms of the patients. Results: At the time of fracture, injured and healthy subjects showed no differences between their bone mineral density (BMD) and bone mineral content (BMC) z -scores at the lumbar spine, or between their BMDs at the peripheral wrist. At cast removal, upper limb bone mineral variables were significantly lower in the injured group (except for the ultradistal radius) than in the uninjured group, with differences ranging from 3.8% to 10.2%. No residual decrease in bone mineral variables was observed at any upper limb site at 6- and 18-month follow-up (28 injured patients). Significant residual increases in the BMDs and BMCs were observed for the injured group's ultradistal radius and whole wrists (+4.8% to +5.2%). Conclusions: A rapid bone mass reversal occurs by resumption of mobilization, with full bone recovery 6 months after a forearm or wrist fracture. Finally, healing bone callus could introduce a bias into the interpretation of BMD and BMC data at the fracture site, not only at cast removal but also 18 months after the fracture.